AB0973 The 8-Joint Ultrasound Score Is Useful for Monitoring Response To Treatment for Rheumatoid Arthritis. (15th July 2016) - Yoshimi, R.; Toyota, Y.; Tsuchida, N.; Sugiyama, Y.; Kunishita, Y.; Kishimoto, D.; Kamiyama, R.; Minegishi, K.; Hama, M.; Kirino, Y.; Ohno, S.; Ueda, A.; et al.
Abstract : Background: Musculoskeletal ultrasonography (US) is one of the standard tools for the diagnosis and monitoring of rheumatoid arthritis (RA). Although we and other groups have proposed several sets of US assessment procedures in arbitrary combinations of selected joints, 1–3 there is still no consensus in defining the joints to evaluate. Objectives: To investigate whether US assessment in the selected 8 joints which we advocate as a routine assessment is useful for monitoring response to treatment for RA. Methods: Power Doppler (PD) US was performed in 24 joints, including all PIP, MCP, bilateral wrist and knee joints, as comprehensive evaluation in 15 RA patients treated with certolizumab pegol (CZP). Before and after treatment with CZP, PD signals were scored semiquantitatively from 0 to 3 in each joint, and total PD oscore-24 and total PD score-8 were calculated by summing up PD scores of the 24 joints and the selected 8 joints (bilateral second and third MCP, wrist, and knee joints), respectively. 1 Results: Amount of change of total PD score-24 by treatment with CZP correlated highly with the changes of disease activity indices, SDAI ( r s =0.91, p <0.01) and DAS28-CRP ( r s =0.86, p <0.01). Although it correlated well with the changes of some components of disease activity indices, including swollen joint count ( r s =0.74, p <0.01), tender joint count ( r s =0.86, p <0.01), CRP ( r s =0.85, p <0.01) and ESR ( r s =0.62, p <0.01), there were no significant correlations between the changes of total PD score-24 and the changes of patient's global assessment ( r s =0.42, p >0.05) and evaluator's global assessment ( r s =0.27, p >0.05). Amount of change of total PD score-8 exhibited stronger correlations with the changes of SDAI ( r s =0.92, p <0.01) and DAS28-CRP ( r s =0.89, p <0.01) as compared to that of total PD score-24 (Figure 1 ). The change of total PD score-8 correlated more highly with the changes of swollen joint count ( r s =0.81, p <0.01) and tender joint count ( r s =0.91, p <0.01), while it showed lower correlation coefficients with the changes of patient's global assessment ( r s =0.39, p >0.05) and evaluator's global assessment ( r s =0.22, p >0.05) as compared to that of total PD score-24. Conclusions: This study suggests that total PD score-8 is useful for monitoring response to treatment in RA patients. References: Yoshimi R, Ihata A, Kunishita Y, et al. A novel 8-joint ultrasound score is useful in daily practice for rheumatoid arthritis. Mod Rheumatol 2015; 25:379–85. Backhaus M, Ohrndorf S, Kellner H, et al. Evaluation of a novel 7-joint ultrasound score in daily rheumatologic practice: a pilot project. Arthritis Rheum 2009;61:1194–201. Naredo E, Rodriguez M, Campos C, et al. Validity, reproducibility, and responsiveness of a twelve-joint simplified power doppler ultrasonographic assessment of joint inflammation in rheumatoid arthritis. Arthritis Rheum 2008;59:515–22. Disclosure of Interest: None declared